Proposed Integrated Control of Zoonotic Plasmodium knowlesi in Southeast Asia Using Themes of One Health - Jessica Scott (Tropical Medicine and Infectious Disease, 2020)
Zoonotic malaria, Plasmodium knowlesi, threatens the global progression of malaria elimination. Southeast Asian regions are fronting increased zoonotic malaria rates despite the control measures currently implemented—conventional measures to control human-malaria neglect P. knowlesi’s residual transmission between the natural macaque host and vector. Initiatives to control P. knowlesi should adopt themes of the One Health approach, which details that the management of an infectious disease agent should be scrutinized at the human-animal-ecosystem interface. This review describes factors that have conceivably permitted the emergence and increased transmission rates of P. knowlesi to humans, from the understanding of genetic exchange events between subpopulations of P. knowlesi to the downstream effects of environmental disruption and simian and vector behavioral adaptations. These factors are considered to advise an integrative control strategy that aligns with the One Health approach. It is proposed that surveillance systems address the geographical distribution and transmission clusters of P. knowlesi and enforce ecological regulations that limit forest conversion and promote ecosystem regeneration. Furthermore, combining individual protective measures, mosquito-based feeding trapping tools and biocontrol strategies in synergy with current control methods may reduce mosquito population density or transmission capacity.